Mangrove Survival Rate Analysis to Measure Rehabilitation Success in Teluk Limau Village, West Bangka Regency - Alamshah, Wahyu; Farhaby, Arthur Muhammad; Adibrata, Sudirman (Akuatik: Jurnal Sumberdaya Perairan, 2023)
West Bangka Regency is an area located in the Bangka Belitung Islands Province, has unique and potential natural resources, and has a coastal ecosystem, namely mangroves. The condition of mangroves is still damaged due to their utilization and management that pays little attention to sustainability aspects. Mangrove rehabilitation carried out in Teluk Limau Village, West Bangka Regency as the main factor preventing abrasion and increasing the economy of coastal communities by planting along the coastline. The purpose of this study was to determine the survival rate and success rate of mangrove rehabilitation and to determine the environmental parameters that affect the survival rate of mangroves in Teluk Limau Village, West Bangka Regency. This research was conducted in July-September 2022 in the Mangrove Rehabilitation area of ​​Teluk Limau Village, West Bangka Regency. Determination of the station using purposive sampling, while for the sampling technique using the transect method squared with a size of 10 m x 10 m. The results obtained are the survival rate of mangroves (Survival rate) ranging from 11.1 to 79.7%. The highest survival rate occurred at station 1 of 79% and the lowest at station 3 of 11.1%. The results obtained indicate a survival rate in the low category or failure in planting. Plant height growth increased by 0.86-1.79 cm/month and leaf growth increased by 1-2 leaves/month. Parameters that affect the survival rate of mangrove rehabilitation is the sand substrate.